PROFITABILITY OF ISLAMIC BANKS: EVIDENCE FROM SHARIA BUSINESS UNIT OF BANK NAGARI - RIZAL RIZAL; DAVID DAVID; HUSNI SHABRI; ELSA FITRI AMRAN (Universitas Islam Negeri Imam Bonjol Padang, 2022)
This study aims to analyze the effect of Total Assets, Non Performing Financing, Financing to Deposit Ratio and Profit Sharing Financing on Return on Assets of Sharia Business Unit of Bank Nagari as Regional Government Bank West Sumatra Province. This type of research is associative research with a quantitative approach. The data analysis technique used ordinal logistic regression model of proportional odds. The results show that partially Non Performing Financing has a negative and significant effect on Return on Assets, Financing to Deposit Ratio has a positive and significant effect on Return on Assets, Total Assets and Profit Sharing Financing has no effect on Return on Assets of Unit Usaha Syariah Bank Nagari. Meanwhile, simultaneously Total Assets, Non-Performing Financing, Financing to Deposit Ratio and Profit Sharing Financing are only able to affect Return on Assets of 41.4%, the rest is influenced by other variables. The research outcomes will be invaluable to Islamic Bank aiming to improve Return on Asset that a decrease in the value of the Non Performing Financing ratio and an increase in the value of the Financing to Deposit Ratio.